Functional and nutritional properties of rambutan (Nephelium lappaceum L.) seed and its industrial application A review - M.H.A. Jahurul; F.S. Azzatul; M.J. Norliza; M. Hasmadi; J.S. Lee; M. Patricia; S. Jinap; M.R. Ramlah George; M. Firoz Khan; I.S.M. Zaidul; Sharifudin Md Shaarani (Elsevier, 2024)
Trends in Food Science & Technology Volume 99, May 2020, Pages 367-374